2011
DOI: 10.1111/j.1365-2338.2011.02463.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Bursaphelenchus xylophilus and Monochamus galloprovincialis in pine branches and wood packaging material

Abstract: Survival and development of Bursaphelenchus xylophilus (pine wood nematode) was studied for up to 40 weeks in Pinus pinaster sawn wood and branches: 30 boards (1200 × 100 × 25 mm), 30 long‐blocks (1200 × 95 × 95 mm), 10 pine branches with bark and nine branches without bark (1200 mm long). The nematode was found in all materials and through the entire sampling period, with higher abundance in the sawn wood (boards and long‐blocks). In the initial period B. xylophilus reproduced abundantly and a population peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The extended presence of nematodes in the openly stored wood chips might be attributed to the continuing availability of some food resources, as suggested by Sousa, Naves, Bonifacio, Inacio, et al. ().…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The extended presence of nematodes in the openly stored wood chips might be attributed to the continuing availability of some food resources, as suggested by Sousa, Naves, Bonifacio, Inacio, et al. ().…”
Section: Discussionmentioning
confidence: 72%
“…The persistence of the PWN at low population densities in our test of long‐term survival suggests that the availability of large amounts of nutritional fungus might not have been necessary (Panesar et al., ; Sousa, Naves, Bonifacio, Inacio, et al. ). Moreover, it is possible that a less prominent fungus was serving as a nutrient source and escaped isolation.…”
Section: Discussionmentioning
confidence: 95%
“…Sousa et al . () followed the survival of B. xylophilus in untreated boards and blocks made from infested trees. They observed a positive correlation between moisture content and nematode prevalence, and reported that initial nematode populations disappeared after 40 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies involving B. xylophilus extraction from wood samples do not mention fungivorous nematodes in their results (Akbulut et al, 2006;Gu et al, 2006), and no information is available on the prevalence of fungivorous nematodes in living or dead wood. Sousa et al (2011) followed the survival of B. xylophilus in untreated boards and blocks made from infested trees.…”
Section: Bursaphelenchus Xylophilusmentioning
confidence: 99%
“…7,46 Although not quantified, all larvae, pupae and adult insects present in the wood were killed with SF fumigation at the three tested temperatures, thereby confirming previous results on the efficacy of SF as an insecticide. 29,32,47,48 The limited survival of the pinewood nematode in low-moisture-content wood 49 and the combined eradication of both the nematode and its insect vector from SFfumigated boards effectively remove the risk of dispersing pine wilt disease, even if low levels of B. xylophilus survive, because the nematode depends on a living vector in the wood for dissemination to a healthy host tree.…”
Section: Discussionmentioning
confidence: 99%